2002
DOI: 10.19173/irrodl.v3i2.101
|View full text |Cite
|
Sign up to set email alerts
|

Student Dropout at the Hellenic Open University: Evaluation of the Graduate Program, "Studies in Education"

Abstract: <p> This study traces the root causes of dropout rates in one post-graduate course “Studies in Education,” offered by the Hellenic Open University (HOU). From our research findings, it was found that the main cause of dropping out stem from a combination of adult learners’ obligations, specifically balancing their academic workload with their employment commitments and family obligations (mainly for female students). The second reason for dropout rates among adult distance education learners includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 4 publications
3
28
0
3
Order By: Relevance
“…This confirms results of previous studies which have identified similar issues associated with time management. For example, in their study on student attrition, Vergidis and Panagiotakopoulos (2002) found that students' overall underestimation of the time and effort required for effective study and learning was the second most cited reason for discontinuing their studies. The most cited reason being unexpected or emergency situations.…”
Section: Resultsmentioning
confidence: 99%
“…This confirms results of previous studies which have identified similar issues associated with time management. For example, in their study on student attrition, Vergidis and Panagiotakopoulos (2002) found that students' overall underestimation of the time and effort required for effective study and learning was the second most cited reason for discontinuing their studies. The most cited reason being unexpected or emergency situations.…”
Section: Resultsmentioning
confidence: 99%
“…Allen et al, 2002). With regard to barriers to completing courses, the main problems appear to be family or work obligations, rather than from factors intrinsic to the course or its delivery (Vergidis and Panagiotakopoulos, 2002). Many studies (Carr et al, 1996;Kerka, 1986;Lazin and Neumann, 1991) indicate that demographic variables are less predictive of completing an educational programme than life circumstances, attitude and the degree of social support received.…”
Section: Resultsmentioning
confidence: 99%
“…In their study of drop-outs from a Hellenic Open University course in education studies, Vergidis and Panagiotakopoulos (2002) found that the main problems stemmed from family or work obligations, rather than from factors intrinsic to the course or its delivery. It has long been known that such external factors were extremely important.…”
Section: Accessibility/barriersmentioning
confidence: 99%
“…For a more detailed study on this group's profile, please refer to Vergidis and Panagiotakopoulos (2002). Of the 349 students who dropped out of "Informatics," almost the entire dropout student population (97 percent) was interviewed.…”
Section: Methodsmentioning
confidence: 99%